Investigation of the Frequency and Types of Errors During the Preparation and Injection of Chemotherapy Drugs - Dehghani Ghorbi, Mahmoud; Homaee, Sina; Saberian, Farnaz; Hadizade, Farnaz; Delkash, Parisa; Akhgarjand, Camellia (Novelty in Biomedicine, 2025)
Background: Medical errors are common in the world, but in some wards and some conditions, they need a higher level of concern. Chemotherapy and its related wards are one of the concerning issues. There are limited studies about the occurrence of medical errors in patients who receive chemotherapy. In this study, we aimed to investigate the frequency and types of errors during the preparation and injection of chemotherapy drugs. Materials and Methods: This cross-sectional study was conducted on patients who were referred to the outpatient chemotherapy department of Imam Hossein Hospital (Tehran, Iran) in 2024. Basic patient data, including age, gender, type of cancer, presence or absence of other underlying diseases, and type of chemotherapy regimen, were extracted. All medication orders during chemotherapy prescribed by the subspecialist physician were reviewed and recorded by the internal medicine specialist assistant under the supervision of the project's supervisory team (clinical specialist, subspecialist, and clinical pharmacy); errors related to the medication process and related to chemotherapy medication errors were identified according to the researcher-made checklist. A statistical significance level was considered less than 0.05. Results: Three hundred patients were evaluated. Medical errors were observed in 247 (82.33%) patients. Medical errors were significantly higher in patients with metastatic cancers than in patients with non-metastatic cancers (P-value: 0.002). No hand washes the most common type of medical error (39.27%), and the most common cause was job burnout (33.60) was the most common cause of medical errors. Conclusion: Medical error frequency during the preparation and injection of chemotherapy drugs in outpatient wards is 82.33%.